Arthritis in childhood human immunodeficiency virus infection predominantly associated with human leukocyte antigen B27. (26th July 2016) - Suri, Deepti; Sharma, Avinash; Bhattad, Sagar; Rawat, Amit; Arora, Sunil; Minz, Ranjana W.; Singh, Surjit
Abstract: Aim: Children with human immunodeficiency virus (HIV) infection usually present with recurrent and unusual infections. Although reported among adults, arthritis as a predominant presentation in children with HIV is rare. Reactive arthritis is considered to be the most common musculoskeletal manifestation in adults with HIV infection. However, in children, septic or HIV‐related arthritis has been described. We report four children having arthritis with HIV disease and their long‐term outcome; out of which three had human leukocyte antigen (HLA)‐B27‐related arthritis. It is important to be aware of arthritic presentation of HIV disease in children to prevent delay in diagnosis and initiation of appropriate therapy. Methods: Clinical profile of children with HIV infection who presented with arthritis and registered at the Pediatric Immunodeficiency Clinic at PGIMER, Chandigarh were reviewed and analyzed. Results: A total of 796 children with HIV infection are registered in the Pediatric Immunodeficiency Clinic since January 1994. Among these, four children had arthritis, and it was the presenting manifestation in two of them. HLA‐B27 related arthritis was noted in three children, while one had HIV‐associated arthritis. None of the children had septic arthritis. Arthritis resolved on treatment with antiretroviral therapy (ART) in two children, while others responded to anti‐inflammatory agents and the joint symptoms remained quiescent on follow‐up with a total follow‐up period of 21.5 patient years. Conclusions: Clinicians must be aware of the arthritic presentation of childhood HIV infection. High degree of suspicion must be entertained to screen for HIV infection in children with arthritis, especially in those with reactive arthritis.